Consumer Data at Risk: Legal Challenges in Personal Data Protection within Shipping Services - Muhamad Najib Hilal Haadii; Moody Rizqy Syailendra (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid expansion of digital commerce and the growing reliance on shipping services have resulted in shipping companies processing substantial volumes of consumers’ personal data, thereby increasing the risk of data misuse and security breaches. This development underscores the need for robust legal protection mechanisms and clear standards of accountability concerning the management of personal data by business actors. This study aims to analyze the legal framework governing the protection of consumers’ personal data in shipping services and to examine the legal liability of business actors for personal data breaches under Law Number 27 of 2022 on Personal Data Protection. Employing a normative legal research method, the study utilizes statutory, conceptual, and analytical approaches through an examination of primary, secondary, and tertiary legal materials. The findings indicate that personal data protection in Indonesia has been comprehensively regulated through the Personal Data Protection Law and its supporting regulations. Furthermore, the legal responsibilities of business actors encompass preventive measures, breach-response obligations, as well as civil, administrative, and criminal liabilities. The study concludes that shipping service providers must implement accountable and transparent data protection governance to ensure legal certainty, strengthen consumer protection, and maintain public trust in the digital economy.